2013
DOI: 10.5194/acp-13-4515-2013
|View full text |Cite
|
Sign up to set email alerts
|

A pervasive and persistent Asian dust event over North America during spring 2010: lidar and sunphotometer observations

Abstract: Among the many well-documented cases of springtime trans-Pacific transport of crustal dust from Asia to North America (significant events include those of 1998, 2001, and 2005), the events of March and April 2010 were extraordinary both in the extent of the dust distribution and in the unique meteorological conditions that caused the dust layers in the free troposphere to linger and be detectable across Canada and the northern United States for over a month. This study focuses on extending previous research by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Fine particulates reaching high altitudes may be transported by tropospheric winds (Shao, 2000;Eguchi et al, 2009). Trans-Pacific transport of mineral dust from East Asia to North America has been frequently detected during springtime (Merrill et al, 1989;Mahowald et al, 1999;Zhao et al, 2003;McKendry et al, 2008;Cottle et al, 2013a). Longrange transport of dust aerosol has been substantiated by ice core samples taken at the North Pole (Jaffe et al, 1999;Mahowald et al, 2017).…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Fine particulates reaching high altitudes may be transported by tropospheric winds (Shao, 2000;Eguchi et al, 2009). Trans-Pacific transport of mineral dust from East Asia to North America has been frequently detected during springtime (Merrill et al, 1989;Mahowald et al, 1999;Zhao et al, 2003;McKendry et al, 2008;Cottle et al, 2013a). Longrange transport of dust aerosol has been substantiated by ice core samples taken at the North Pole (Jaffe et al, 1999;Mahowald et al, 2017).…”
mentioning
confidence: 92%
“…Unfortunately, lidar observations in Beijing were not possible on 6 May due to routine maintenance. In the lidar measurement for this study, the well-mixed boundary layers in East Asia, prior to the obvious intermingling of subsiding layers from above, show depolarization ratios 150-250 % higher than boundary layers in North America (Cottle et al, 2013a). This indicates that dust clouds moved across the North China Plain at altitudes < 1500 m. Our lidar observations of dust being uplifted to altitudes of 3.5 km above the Korea Peninsula and Japan agree closely with those of Murayama et al (2001) who observed dust being uplifted to altitudes of 3 km over Japan and 4-5 km over the Korean Peninsula as a result of a wind erosion event in northwestern China and Mongolia in 1998.…”
Section: Vertical and Horizontal Dust Dispersionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported that Asian dust aerosols can be transported to vast downwind areas, including the coastal seas of China, Korea, Japan, and even North America (Fang et al, 1999;Mori et al, 2002;Zhao et al, 2011;Cottle et al, 2013;Li et al, 2015). These transported aerosols are often mixed with high concentrations of regional pollution aerosols that largely reduce visibility and worsen air quality in downwind areas of East Asia (Guo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%